“Control Interno y su incidencia en la gestión administrativa de la empresa de RapiRaptor Cía., Ltda., del Cantón La Maná, provincia de Cotopaxi” - Gallo Castillol, Sandy Clarive (2021)
This research was focused on developing an internal control system and the incidence on administrative management in the service company RapiRaptor Cía. Ltda., from La Maná Canton, Cotopaxi province, the new information that it contributes to society is the structuring of systematic processes that can be adapted in different entities, promoting innovative growth at institutional level; within the offered services by the entity, it will be benefitted from knowing in detail the impact of adequate control to promote an adequate competitive framework. The cause of this investigation is that RapiRaptor company does not have an internal control system that allows determining an adequate development of the administrative aspect, the scientific descriptive investigation was applied. In order to carry out internal control in the company, research techniques like surveys were applied to the employees, the interview to the directors, and the internal control sheets to consolidate the analysis of the five components of the company and, based on this, to establish the real situation of the entity to strengthen the growth of the entity and promoting the competitive level of each of the services provided by the entity. The results established that the processes at the level of Administrative Management in the RapiRaptor company are not visualized through efficiency indicators due to the absence of them. The company demonstrates that there is a very high percentage of procedures that are not planned, and reduces the level of compliance of the goals and objectives that are generated. It was established as a conclusion that in order to improve the functional development of RapiRaptor Cía. Ltda., it is necessary to strengthen the strategic direction by establishing the mission, vision, corporate values, organizational structure, and functional processes that allow establishing a functional systematic process.